2016
DOI: 10.1186/s40064-016-2569-7
|View full text |Cite
|
Sign up to set email alerts
|

Habitual dietary protein intake affects body iron status in Japanese female college rhythmic gymnasts: a follow-up study

Abstract: BackgroundMany rhythmic gymnasts stay lean by reducing their body weight (BW); however, this may result in iron deficiency (ID). Our previous cross-sectional study reported an association between ID incidence and protein intake in gymnasts during the pre-season. The present study aimed to examine the association between dietary protein intake and ID incidence in a 2-year follow-up study.MethodsElite Japanese female college rhythmic gymnasts [mean age ± standard deviation (SD): 18.4 ± 0.5 years] were recruited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…This finding was in agreement with the finding which is reported by a study done in Japan that protein intake may reduce iron deficiency among females. 50 This result is supported by Indonesia Baseline Health Research, that adolescents in Indonesia consume fewer vegetables, where vegetables are a source of protein.…”
Section: Discussionmentioning
confidence: 80%
“…This finding was in agreement with the finding which is reported by a study done in Japan that protein intake may reduce iron deficiency among females. 50 This result is supported by Indonesia Baseline Health Research, that adolescents in Indonesia consume fewer vegetables, where vegetables are a source of protein.…”
Section: Discussionmentioning
confidence: 80%
“…There is a possibility that protein and fat intake may have been limited in August. Previously, we had reported an association between insufficient protein intake and a high risk of the incidence of ID 13,20) . Animal-based food groups including meats, seafood, and poultry contain more heme iron and are the most important protein sources in people's daily lives.…”
Section: Discussionmentioning
confidence: 96%
“…To maintain their ideal sports-specific body shape involved with artistic beauty, female rhythmic gymnasts often strive to lose weight, which includes restricting or skipping meals during the pre-season period before major competitions 11,12) . This could result in ID, and in fact, the incidence rate of ID in rhythmic gymnasts during the preseason (August) in rhythmic gymnasts was 51% 13) . During the pre-season (July and August), we measured both delta-aminolevulinic acid dehydratase (ALAD) activity 14) as an indicator of RBC synthesis and serum haptoglobin (Hp) concentrations 15) as an indicator of hemolysis, and reported that in Japanese female collegiate rhythmic gymnasts, in August compared to July 16) or June 17) , ALAD activity was elevated and Hp levels were decreased.…”
Section: Introductionmentioning
confidence: 99%
“…The average student energy intake in this study was below the normal Nutrition Adequacy Rate for adolescent girl aged 15 -18 years old (2125 Kcal per day), but their protein intake was sufficient. Proteins are important compounds that have a key role in the formation of red blood cells and prevention of anemia (Kokubo et al, 2016;Wu, 2016).…”
Section: Discussionmentioning
confidence: 99%